Cross-sector Collaboration With HIV NGOs At Kedungdoro Primary Health Care - Wijaya, Andriana Putri; Arizka, Ulfa Dwi; Wulandari, Ratna Dwi (Griya Eka Sejahtera, 2025)
Background: Indonesia is the country with the 3rd highest number of new HIV cases in Asia Pacific after India and China. Surabaya is the city with the most HIV cases discovered with 1,260 cases. The indicator of the success of the HIV program is related to the number of people with new HIV who are found and given treatment, namely 43 out of 63 (68.25%) Primary Health Cares, the number of findings is less than the average for Primary Health Cares in Surabaya City, namely 8 PLHIV in 2023. Kedungdoro Health Center is a health center with the highest number of people with new HIV discovered and given treatment, namely 78 PLHIV in collaboration with various NGOs in HIV programs including Orbit, Mahameru, PKBI, JIP, Surabaya plus, Gaya Nusantara. This collaboration, which has existed for more than 10 years, can help increase the achievements of the HIV program, therefore the aim of this article is as a good practice that can be used as a reference by Primary Health Cares to improve the achievements of the HIV program from the aspect of cross-sector collaboration, especially NGOs.customers, PLHIV, prospective brides and grooms and the general public.Methods: The research method used is a qualitative method. The data collection technique was carried out by collecting primary data and secondary data. Primary data was obtained through in-depth interviews The triangulation used in this research uses triangulation of data sources in the form of the results of in-depth interviews and observations.Results: Steps to build collaboration across NGO sectors in handling HIV AIDS include: 1. Ensure that the Primary Health Care has been appointed by the Health Service as a provider of PDP (Care, Support, Treatment Services). 2. Separate the VCT poly from the other poly. 3. Puskesmas must have a minimum of 1 trained counselor, 1 case manager, and 1 RR or HIV data processing admin. 4. Puskesmas prepares a decision letter from the HIV prevention and control team, terms of reference for activities, and implementation SOPs. 5. Primary Health Cares can apply to the Health Service to collaborate with NGOs or Primary Health Cares can contact relevant NGOs in an effort to establish collaboration. 6. Primary Health Cares make efforts to innovate HIV programs. 7. Puskesmas evaluates the HIV program.Conclusion: he management of the HIV program at the Kedungdoro Health Center in collaboration with HIV NGOs has gone well so that the Kedungdoro Health Center's achievements will be the highest in the city of Surabaya in 2023 regarding indicators